Extendible commercial notes - alternatywa dla tradycyjnych krótkoterminowych papierów dłużnych - Pauka, Marek (Extendible Commercial Notes - the Alternative for Traditional Commercial Paper, 2005)
This article shows one of the new kinds of commercial paper - Extendible Commercial Notes. These debt securities add new options for issuers and transfer market disruption risk from traditional financial institution founded liquidity lines to investors. The pros and cons for offering ECNs on the Polish money market are also considered.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 94-104